Efficacy of antibiotic treatment in patients with chronic low back pain and Modic changes (the AIM study): double blind, randomised, placebo controlled, multicentre trial. (16th October 2019) - Bråten, Lars Christian Haugli; Rolfsen, Mads Peder; Espeland, Ansgar; Wigemyr, Monica; Aßmus, Jörg; Froholdt, Anne; Haugen, Anne Julsrud; Marchand, Gunn Hege; Kristoffersen, Per Martin; Lutro, Olav; Randen, Sigrun; Wilhelmsen, Maja; et al.
Abstract: Objective: To assess the efficacy of three months of antibiotic treatment compared with placebo in patients with chronic low back pain, previous disc herniation, and vertebral endplate changes (Modic changes). Design: Double blind, parallel group, placebo controlled, multicentre trial. Setting: Hospital outpatient clinics at six hospitals in Norway. Participants: 180 patients with chronic low back pain, previous disc herniation, and type 1 (n=118) or type 2 (n=62) Modic changes enrolled from June 2015 to September 2017. Interventions: Patients were randomised to three months of oral treatment with either 750 mg amoxicillin or placebo three times daily. The allocation sequence was concealed by using a computer generated number on the prescription. Main outcome measures: The primary outcome was the Roland-Morris Disability Questionnaire (RMDQ) score (range 0-24) at one year follow-up in the intention to treat population. The minimal clinically important between group difference in mean RMDQ score was predefined as 4. Results: In the primary analysis of the total cohort at one year, the difference in the mean RMDQ score between the amoxicillin group and the placebo group was −1.6 (95% confidence interval −3.1 to 0.0, P=0.04). In the secondary analysis, the difference in the mean RMDQ score between the groups was −2.3 (−4.2 to−0.4, P=0.02) for patients with type 1 Modic changes and −0.1 (−2.7 to 2.6, P=0.95) for patients with type 2 Modic changes. Fifty patients (56%) in the amoxicillin group experienced at least one drug related adverse event compared with 31 (34%) in the placebo group. Conclusions: In this study on patients with chronic low back pain and Modic changes at the level of a previous disc herniation, three months of treatment with amoxicillin did not provide a clinically important benefit compared with placebo. Secondary analyses and sensitivity analyses supported this finding. Therefore, our results do not support the use of antibiotic treatment for chronic low back pain and Modic changes. Trial registration: ClinicalTrials.gov NCT02323412 .